Retaining doctors in rural Bangladesh: A policy analysis - Joarder, Taufique; Rawal, Lal B.; Ahmed, Syed Masud; Uddin, Aftab; Evans, Timothy G. (International Journal of Health Policy and Management, 2022)
This article was published in the International Journal of Health Policy and Management [© 2018 The Author(s); Published by Kerman University of Medical Sciences. This is an open-access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0) ] and the definite version is available at: https://doi:10.15171/ijhpm.2018.37 The Journal's website is at: https://www.ijhpm.com/?_action=articleInfo&article=3495&lang